PENGARUH BRAND IMAGE (CITRA MEREK) TERHADAP PREFERENSI KONSUMEN DALAM MEMBELI BUAH PISANG ‘SUNPRIDE’ DI KOTA YOGYAKARTA - Agni Novita Sari; Danang Manumono; Ari Astuti (Fakultas Pertanian UST, 2019)
As we know that the current product offer is very diverse and numerous, including agricultural products, especially fresh fruits. Banana is a fruit commodity that is favored by many people in Indonesia, but the branding of its comodity in Indonesia is still lacking. By knowing the preference of consumer for banana, in this research using the brand from SUNPRIDE, the writer want to know how the brand image ot its comodity. This study aims to determine the effect of brand image, price, and income on consumer preferences in buying Sunpride bananas in the city of Yogyakarta. The basic method used is descriptive method. The sampling method uses accidental sampling with 40 respondents. The method of data analysis uses multiple linear regression analysis with the test coefficient of determination, F test, and partial t test (α = 0.05). The results of the study show that brand image and revenue have a positive and significant effect on consumer preferences. While prices do not significantly affect consumer preferences.